Comparison of Types of Inpatient Services for BPJS Patients and Non BPJS Patients with Patient Satisfaction Level - Haerani; Haerati; Fina Magfira (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Patient satisfaction is an indicator of the quality of service we provide and patient satisfaction is a capital to get more patients to get loyal patients. Factors that influence patient satisfaction are product or service quality, price, emotional, performance, service, facilities, atmosphere, and communication. This study aims to determine inpatient services for BPJS and Non-BPJS patients with the level of patient satisfaction in H. Andi Sulthan Daeng Radja Bulukumba Hospital, This study is an analytic observational study with a comparative approach study. This sampling uses a nonprobability sampling method with the sampling technique is a consecutive sampling. The research sample taken amounted to 76 respondents each 38 BPJS patients and 38 Non-BPJS patients from a total population of 305 patients conducted in the inpatient room of H. Andi Sulthan Daeng Radja District Hospital. Bulukumba from May 16 to May 18, 2017. The measuring instrument used was a questionnaire with a Likert scale. The results of this study were 76 respondents from 38 BPJS patients and 38 Non-BPJS patients, from 38 BPJS patients, who were dissatisfied with 6 respondents (7,895), who were satisfied as many as 27 respondents (35,526%), who were very satisfied as many as 5 (6.679%) while from 38 Non-BPJS patients there were no dissatisfied patients, 27 respondents were satisfied (35,526%), who were very satisfied as many as 11 respondents (14.479%). The conclusion was that there were differences in the level of service satisfaction inpatients given to BPJS patients and Non-BPJS patients at H. Andi Sulthan Daeng Radja Bulukumba Hospital in 2017 with p = 0.032 <a = 0.05